Policy Advocacy for a Climate Smart Food System in South East Asia: Seed Systems Research Study - Tiongco, Marites M.; Baruah, Sampriti; Mohanty, Samarendu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This study investigated the various aspects of seed systems of climate resilient root and tuber crops, which includes seed value chain, seed replacement and certification procedure, varietal release process, and seed trade and market, in the Philippines. The study focused on three most important root and tuber crops of cassava, sweetpotato and potato. The findings of the study will be helpful to identify challenges and opportunities to improve efficiency of seed systems to accelerate adoption of climate-resilient crops. Value chain analysis approach to map the interaction among stakeholders involved in the seed production activities and trade, and Strengths-Weaknesses-Opportunities-Threats (SWOT) analysis to assess the overall performance of the seed value chain were used as methodology. Data collected are from secondary sources and primary data using focus group discussion and key informant interview.